Nature of Rous Sarcoma Virus-Specific RNA in Transformed and Revertant Field Vole Cells - Krzyzek, Richard A. (1979)
Cytoplasmic and polyribosomal RNAs from Rous sarcoma virus-transformed and phenotypically reverted field vole cells were fractionated by rate-zonal sedimentation and hybridized with a (3)H-labeled complementary DNA viral probe to determine the size classes of virus-specific RNA present in these cell types. In contrast to Rous sarcoma virus-infected permissive avian cells, only two of three discrete species of virus-specific RNA were detected in the cytoplasm of these vole cells. These included genome-length 35S RNA and a 21S RNA. However, viral 28S RNA, routinely detected in the cytoplasm of productively infected avian cells, could not be found in cytoplasmic RNA from vole cells. In addition, a low-molecular-weight viral RNA sedimenting less than 16S was detected in both infected avian and vole cells. Because of its heterogeneity this latter species is most likely generated from the intracellular degradation of the larger viral RNAs. Both the viral 35S and 21S RNA were also found to be associated with total polyribosomes from these vole cells. Studies were also performed to determine the distribution of both total viral genomic and sarcoma-specific RNA sequences among the size classes of fractionated total polyribosomes. In both vole cell types the majority of cytoplasmic viral RNA sequences were also associated with polyribosomes and were similarly distributed among the size classes of total polyribosomes. Sarcoma-specific sequences were present on both the 35S and 21S RNA species. These data suggest that the expression of the viral transforming gene in revertant field vole cells may be controlled at some stage subsequent to translation of the viral RNA.